Anti-collision Analysis of Pad Drilling and Optimization of Wellbore Trajectory: A Field Case Study - Al-Rubaye, Wisam I.; Ghanem, Dhiaa S.; Saleem, Ali M.; Al-Attabi, Hayder A. (Journal of Petroleum Research and Studies, 2022)
Errors can occur in the wellbore position according to the fact the survey tools are not completely accurate; therefore, prediction of well path position is imperative for safe and cost-effective drilling operation. The aim of this paper is an analysis of collision avoidance as well as assessment and optimization of wellbore trajectory for minimizing the risk of collision by applying different anti-collision and planning techniques. Thus, anti-collision analysis of pad drilling in the Iraqi oil field has been investigated using Industry Steering Committee for Wellbore Survey Accuracy (ISCWSA) error model to estimate the wellbores position and assess their separation using different techniques available in the industry. Three actual offset wells X1, X2, X3, and one proposed principal X4 well in a drilling pad have been used in the collision avoidance model. Separation factor, ladder, and travel cylinder plots revealed a high possibility of X4 proposed well colliding with X3 actual offset well. The separation factor of 0.75 and 7.5 m center to center prove that the current design of X4 principal design doesn’t meet the anti-collision standards, accordingly, a design revision must be highly considered. The field operator hasn’t revised the well design due to the lack in the assessment of anti-collision risks, thus, the survey service company has advised the operator to modify the predetermined well trajectory due to major risk of collision with X3 offset well and the well has been sidetracked. After reviewing and optimizing the well trajectory by using slant and optimum align (curve hold curve) planning methods, the anti-collision results have been greatly improved. The results showed that, through adopting an adequate anti-collision risk assessment and the modified well design, problems associated with the execution of the improper well design could be totally eliminated.